THE SCHOOL FOR GOOD AND EVIL: THE LAST EVER AFTER NOVEL BY SOMAN CHAINANI - Yanti Rosalinah; Ibnu Subroto; Retno Rahayuningsih; Tias Mawarni (Sean Institute, 2023)
This study has objectivity towards the manipulative treatment carried out by the characters in the third novel The School for Good and Evil, namely The Last Ever After. Research on manipulative behavior is focused on the characters of Rafal and Sophie. The purpose of this study is to find out and warn readers about manipulative behavior in romantic relationships and how it can be dangerous for the victim. In doing this research, the writer uses several theories to classify each manipulative treatment performed by the characters. After knowing the signs and types of each manipulative treatment, the writer then analyzes how the treatment influences Sophie's character throughout the story. From the data that has been collected, it can be concluded that Sophie's character experiences an inability to trust herself in doing something and ultimately depends on Rafal in making decisions even though she knows that this is dangerous for other people safety.